Macrophage expression of tartrate-resistant acid phosphatase as a prognostic indicator in colon cancer - How, Joan (2014)
Recent research has indicated that separate populations of macrophages are associated with differing outcomes in cancer survival. In our study, we examine macrophage expression of tartrate resistant acid phosphatase (TRAP) and its effect on survival in colon cancer. Immunohistochemical analysis on colorectal adenocarcinomas confirmed macrophage expression of TRAP. Co-localization of TRAP with CD68, a pan-macrophage marker, revealed that TRAP is present in some but not all subpopulations of macrophages. Further co-localization of TRAP with CD163, an M2 marker, revealed that TRAP is expressed by both M2 and non-M2 macrophages. TRAP expression was then measured using the AQUA method of quantitative immunofluorescence in a tissue microarray consisting of 233 colorectal cancer patients seen at Yale-New Haven Hospital. Survival analysis revealed that patients with high TRAP expression have a 22% increase in 5-year survival (uncorrected log rank p=0.025) and a 47% risk reduction for disease specific death (p=0.02). This finding was validated in a second cohort of older cases consisting of 505 colorectal cancer patients. Patients with high TRAP expression in the validation set had a 19% increase in 5-year survival (log rank p=0.0041) and a 52% risk reduction of death (p=0.0019). These results provide evidence that macrophage expression of TRAP is associated with improved outcome, and implicates TRAP as a potential biomarker in colon cancer.